The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s1415-790x2010000300015
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição espacial das internações por asma em idosos na Amazônia Brasileira

Abstract: Introduction: In Brazil, there are approximately 370,000 asthma-related hospitalizations per year, representing the fourth leading cause of hospitalizations in public health services. In 2007, 157,000 elderly patients were hospitalized, 2.3% of which due to asthma in the Brazilian Amazon. The rate of hospitalizations during the dry season was as much as three times that of the rain and intermediate seasons, with the highest rates in Rondônia (5.8 ‰) and Mato Grosso (3.3 ‰). Conclusion: Asthmarelated hospital a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
(36 reference statements)
0
3
1
11
Order By: Relevance
“…Rodrigues et al 34 found that the highest rates of hospitalization for asthma among elderly people in the Brazilian Amazon has occurred in the drought season, which is in disagreement with the Valença et al 14 We conclude that the hospitalizations of children for asthma are more frequent in the months of more intense rainfall, with greater magnitude in the states that comprise the "arc of deforestation" in the Brazilian Amazon, especially Rondônia and Maranhão.…”
Section: Gina -Globalcontrasting
confidence: 64%
“…Rodrigues et al 34 found that the highest rates of hospitalization for asthma among elderly people in the Brazilian Amazon has occurred in the drought season, which is in disagreement with the Valença et al 14 We conclude that the hospitalizations of children for asthma are more frequent in the months of more intense rainfall, with greater magnitude in the states that comprise the "arc of deforestation" in the Brazilian Amazon, especially Rondônia and Maranhão.…”
Section: Gina -Globalcontrasting
confidence: 64%
“…4,12 A time series analysis study carried out in the city of Piracicaba, SP, Southeastern Brazil, in 1997 and 1998 quantifi ed daily hospital admissions for RD in children, adolescents and elderly aged > 65. 4 There was a 32.05 increase in the number of hospitalizations for RD in children and adolescents, associated with interquartile variation of PM 10 Cases requiring hospitalization are at higher risk than those which require medical consultation in the primary care network. In this study, it was not possible to conduct a survey of outpatient care, which impedes evaluation of the risks which pollution from PM 2.5 may present for respiratory disease requiring less complex levels of care.…”
Section: Resultsmentioning
confidence: 99%
“…Although evidence exists demonstrating the risks posed by smoke from burning tropical forests on the health of the exposed population groups, the few epidemiological studies which have been carried out in this region are very recent. 10 This study aimed to analyze the effects of exposure to fi ne particles from burning biomass on hospitalizations for respiratory disease in children and the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Rodrigues et al 34 verificaram que as maiores taxas de hospitalização por asma em idosos na Amazônia brasileira têm ocorrido no período de seca, contrapondo-se ao estudo de Valença et al 14 . Alguns fatores inerentes à população idosa podem explicar esse achado.…”
Section: Discussionunclassified